Shape Memory Alloys for Civil Engineering - Fang, Cheng; Qiu, Canxing; Zheng, Yue (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This overview of the most recent advances in the field of SMA research and applications in civil engineering aims to help remove the knowledge barriers across disciplines and sheds considerable light on the opportunity to commercialize SMA products in the construction industry.